Effect of oxidant on the performance of conductive polymer films prepared by vacuum vapor phase polymerization for smart window applications. (10th February 2015) - Brooke, Robert; Fabretto, Manrico; Vucaj, Nastasja; Zuber, Kamil; Switalska, Eliza; Reeks, Lachlan; Murphy, Peter; Evans, Drew
Abstract: Conductive polymers synthesized by vacuum vapour phase polymerization (VPP) were investigated and optimized by changing the oxidant solution and VPP chamber parameters for their incorporation into 'smart window' electrochromic devices. Additionally, the interaction of two oxidant solutions with typical electrode materials (aluminium and indium tin oxide) were examined with respect to material etching, device cosmetics and long term device degradation (over 10 000 switch cycles). Devices made with conducting polymers synthesized with the oxidant Fe(Tos)3 rather than FeCl3 produced superior device performance with respect to optical switching range (% T ), switch speed and optical relaxation.